Effect of Different Types and Times of Mulching on the Success and Economics of Afforestation in Semi-arid Ravinous Tract of Gujarat - Singh, Bakhshish; Pradhan, I. P.; Singh, A. (Indian Forester, 1977)
An experiment comprising of six treatments based on combination of three types and two times of mulching and four replications was conducted during 1967-1972 at the Soil Conservation Researeh Station, Vasad (Gujarat) to study their effect on comparative success and cost of afforestaion in a semi-arid ravinous tract. The results show that clod mulching (Soil hoeing without pulverisation and spreading clods on the surface in one meter diameter around plants) in post-monsoon period (October) gave significantly better height and diameter growth of khair (Acacia cateshu) plants as compared to grass mulching or the usual weeding and hoeing. Clod mulching in October also gave higher survival % of the plants and was overall cheaper in cost than the prevalent practice of weeding and hoeing.